The Impact of Debt Management on the Economic Development of Nigeria - Onyeka-Iheme, Chimeruo Victory; Ekle, Jerome Achadu; Iheme-Madukairo, Onyekachi; Damian, Henry Roosevelt (International Journal of Economics and Financial Issues, 2025)
Debt can serve as a fiscal policy tool to enhance a nation's economic growth if managed efficiently. Government debt management is a response initiative used to stabilize the economy while ensuring sustainable growth. This study examined the effect of debt management on economic growth in Nigeria. Ex-post facto research design was employed for the study. The study’s population encompassed the Nigerian economy, as measured through debt management and economic growth indicators, over thirty years from 1994 to 2023. The total enumeration sampling technique was employed. Data for the research were obtained from Nigeria’s Statistical Bulletin, the Debt Management Office, and the National Bureau of Statistics. Data were analyzed using E-views (version 12.0) to produce both Descriptive and Inferential statistics (ARDL regression). The findings revealed that debt management significantly affects economic growth (Adj.R2= 0.47, F (3, 26) = 26.26, p<0.05). The study concluded that debt management has a significant impact on economic growth in Nigeria. The study recommended that the government should adopt prudent debt management strategies, such as prioritizing concessional loans, reducing the share of external debt, and ensuring that borrowed funds are channeled into productive sectors for high returns.